A study on the hydrogen storage performance of graphene–Pd(T)–graphene structure. (21st April 2020) - Tian, Weizhi; Zhang, Ying; Wang, Yazhou; Liu, Tong; Cui, Hong
Abstract: The 1–6 H2 molecule adsorption energy and electronic properties of sandwich graphene–Pd(T)–Graphene (G–Pd(T)–G) structure were studied by the first-principle analysis. The binding energies, adsorption energies, and adsorption distances of Pd atoms-modified single-layer graphene and bilayer graphene with H2 molecules at B, H, T adsorption sites were calculated. In bilayer graphene, the adsorption properties at T sites were found to be more stable than those at B and H sites. The binding energy of Pd atoms (4.16 eV) on bilayer graphene was higher than the experimental cohesion energy of Pd atoms (3.89 eV), and this phenomenon eliminated the impact of metal clusters on adsorption properties. It was found that three H2 molecules were stably adsorbed on the G–Pd(T)–G structure with an average adsorption energy of 0.22 eV. Therefore, it can be speculated that G–Pd(T)–G is an excellent hydrogen storage material. Highlights: Construct G - Pd(T) - G sandwich structure. Comparison of adsorption site stability of H2 molecule. Threshold test of adsorption of hydrogen by the system. After hydrogen absorption, the structure and electron properties change.